Percepção de crianças e adolecentes em tratamento oncológico sobre a hospitalização - Souza, Raíra Lopes Amaral de (2019)
Introduction: Cancer is a group of several diseases having in common the uncontrolled proliferation of abnormal cells and can occur anywhere in the body. Currently, cancer is considered a public health issue, and when it occurs in children and adolescents it presents several peculiarities that impact on their quality of life and depends on the care of several nuclei and professional fields. Objective: To know the perception of children and adolescents in oncological treatment of hospitalization. Methodology: This is a qualitative research paper, of descriptive-exploratory type that uses the semi-structured interview mediated by the drawing technique for the production of the data. The data collection took place from May to November 2018. For the analysis of the data coming from this research, we used the thematic and inductive analysis. The Resolutions of the Research Ethics Committee were respected and obtained approval under number of opinion CAAE 857746.8.0000 5346. Results: Three categories emerged: The professional communication with the hospitalized child and adolescent, social isolation during the hospitalization process and the importance of play activities during the hospitalization. Final considerations: We suggest the implementation of public policies, such as the National Humanization Policy and the principles of palliative care for caring qualification and the permanent education of professionals who treat these children and adolescents.